Effect of lysophosphatidic Acid on the Vascular Endothelial Growth Factor Expression in Autotransplanted Mouse Ovaries Encapsulated in Sodium Alginate - Maryam Dehghan; Shirin Shahbazi; Mojdeh Salehnia (Tehran University of Medical Sciences, 2021)
Objective: The aim of this study was to evaluate the effect of lysophosphatidic acid (LPA) supplementation during in vitro culture and transplantation of mouse ovaries on the follicular development and expression of vascular endothelial growth factor (VEGF) as an angiogenesis factor at the mRNA and protein levels. Materials and methods: Three weeks old mice ovaries were cultured in the presence and absence of LPA for 24 hours, then they were capsulated in sodium alginate in the presence and absence of LPA as four experimental groups. After transplantation the vaginal smears were performed daily to evaluate the initiation of the estrous cycle. The morphology and follicular distribution were analyzed at the first and fourth estrous cycles using hematoxylin and eosin staining. Then in the groups that showed higher and lower follicular development the immunohistochemistry assay was conducted to identify VEGF protein expression, and the real time RT-PCR was done to analyze the expression of Vegf gene at the first estrus cycle. Results: The large size follicles and also the corpus luteum were prominent in all transplanted groups at fourth estrus cycle in comparison with intact control groups. The statistically lowest percentage of small size follicles and the highest percentages of large size follicles were seen in LPA+/LPA- group (p<0.05). The expression ratio of Vegf to β-actin was significantly higher in this group in comparison with non-LPA treated and intact control groups (p <0.05). Conclusion: LPA as an angiogenesis factor increases the follicular development in transplanted ovaries but it causes early discharge of ovarian reserve.